(untitled) (Sport - nauka i praksa, 2024)
The aim of this empirical study was to examine the latent structures of adolescents’ interest in sports. The pertinent sample included (N = 144) male high school seniors from Valjevo, of average age 18.05 ± 1.82. The adapted version of the PS2 Questionnaire about Interests in Sports (Prot and Bosnar, 1999) was applied in this transversal research. The maximum mean value of the scores on the PS-2 questionnaire was noted in the preference for auto and motorcycle racing (M = 3.72), and the minimum one in gymnastics (M =1.10). Five main components were extracted by analyzing the main components (PCA) based on the Guttman-Kaiser criterion, with 6.91% of the total variance explained. The extracted five-factor structure of the latent dimensions was interpreted as: outdoor sports, combat sports and martial arts, fundamental and artistic sports, ball and racket sports, and precision sports. The linear correlations of the isolated common factors are statistically significant (p ≤ 0,05), move in positive direction and are of low or moderate intensity, and that shows that the isolated latent variables are not independent, but that there is a relevant overlap between them. The preference of sports interests in the five-factor structure of adolescents is oriented towards “male” and partly towards “neutral” sports which points to the relevance of gender stereotypes in sports. This study also deals with the practical implications of the relevance of the isolated five-factor structure of sports interest in adolescents. This transversal research contributes to the existing literature and empirical data on this rarely examined phenomenon in Serbian sports population.